Acceptance and willingness to pay for solar home system: Survey evidence from northern area of Pakistan. (November 2017) - Abdullah,; Zhou, Deyi; Shah, Tariq; Jebran, Khalil; Ali, Sajjad; Ali, Asad; Ali, Asad
Abstract: The importance of solar energy has been accepted worldwide for the generation of electricity, but unfortunately, Pakistan has yet to exert efforts on the development of this source of energy. The purpose of this research is to explore the public acceptance and interest in solar home system (SHS). Moreover, the expectations of the public towards SHS development in Pakistan and the difficulties they face in SHS usage are identified. The result of the survey indicates that about 81% of the respondents show higher interest in SHS. However, many respondents claim that some hindrances obstruct them from using SHS which includes; high cost of solar panels, lack of information and trust on solar panel providers. Almost 60% of the respondents expect that government provision of incentives could be the best way to boost the usage of SHS countrywide. For the successful implementation of new SHS policy, the government of Pakistan needs to establish solar power plants, increase installation of solar panels, provides funding and full information for conducting independent research. In addition, almost 90% of the respondents believe that government should take the lead in developing the SHS sector. Therefore, this study provides some valuable references for SHS promotion in Pakistan.